Ultrahigh‐Output Triboelectric and Electromagnetic Hybrid Generator for Self‐Powered Smart Electronics and Biomedical Applications. Issue 40 (8th September 2022) - Rana, S. M. Sohel; Salauddin, M.; Sharifuzzaman, Md; Lee, Sang Hyun; Shin, Young Do; Song, Hyesu; Jeong, Seong Hoon; Bhatta, Trilochan; Shrestha, Kumar; Park, Jae Yeong
Abstract: Biomechanical energy harvesting shows great potential in the fields of smart electronics and biomedical Internet of Things. However, it is a significant challenge to develop a biomechanically driven energy harvester with high output power and fast charging as a sustainable power source for extended practical applications. Herein, an ultrahigh‐output triboelectric and electromagnetic hybrid generator (UHO‐TEHG) is developed to efficiently harvest biomechanical energy and provide self‐powered systems for numerous applications. The Halbach magnet array is used to concentrate additional magnetic flux in the coil and significantly enhance electromagnetic performance, while the novel poly(ethylene oxide) nanofibers enhance the triboelectric performance. Through the implementation of a mechanical spring‐mass model, and rational integration of electromagnetic and triboelectric generators, the UHO‐TEHG can provide an excellent output power of 1.02 W. Compared with existing mechanical energy harvesting devices, the fabricated device exhibits a much faster battery charging performance. Experimental results reveal remarkable performance related to biomechanical energy harvesting during walking, running, hiking, mountaineering, and self‐powered wireless human motion sensor. Real‐time charging of smartphones, smartwatches, Buds Live, and iTag via customized power management circuits is demonstrated. In addition, the fabricated UHO‐TEHG demonstrates the capability to power healthcare monitoring systems using a laser‐induced hierarchical carbon nanofiber‐based e‐tattoo sensor. Abstract : Poly(ethylene oxide) nanofiber and Halbach magnet array‐based ultrahigh‐output triboelectric and electromagnetic hybrid generators are developed for harvesting biomechanical energy. Based on this performance, fast charging smartphones, smartwatches, Buds Live, iTag, real‐time self‐powered wireless healthcare monitoring systems, and human motion sensor systems via customized power management circuits are demonstrated.